2019
DOI: 10.1007/s13165-019-00262-6
|View full text |Cite|
|
Sign up to set email alerts
|

Undersown cover crops have limited weed suppression potential when reducing tillage intensity in organically grown cereals

Abstract: Adoption of reduced tillage in organic cropping has been slow, partly due to concerns about increasing weed infestation. Undersown cover crops (CCs) are considered to be a feasible option for weed management but their potential for weed suppression is insufficiently investigated in low-till organic cropping. The possibilities to reduce primary tillage by introducing CCs to maintain weed infestation at a level that does not substantially jeopardize crop yield were studied in a field experiment in southern Finla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…At the same time, incentives for farmers were introduced in many countries with the aim to reduce soil cultivation and to preserve soil structure and moisture and prevent erosion. Unfortunately, reduced tillage tends to favor perennial weed species, thus changing the composition of plant populations towards species which are difficult to control and have a high crop yield reduction potential (e.g., [72,73]). Glyphosate made it possible to control E. repens and some other perennial weeds as well as overwintering annual species such as Tripleurospermum inodorum, Stellaria media, and Poa annua when reducing tillage [74,75].…”
Section: History Of Elymus Repens Controlmentioning
confidence: 99%
“…At the same time, incentives for farmers were introduced in many countries with the aim to reduce soil cultivation and to preserve soil structure and moisture and prevent erosion. Unfortunately, reduced tillage tends to favor perennial weed species, thus changing the composition of plant populations towards species which are difficult to control and have a high crop yield reduction potential (e.g., [72,73]). Glyphosate made it possible to control E. repens and some other perennial weeds as well as overwintering annual species such as Tripleurospermum inodorum, Stellaria media, and Poa annua when reducing tillage [74,75].…”
Section: History Of Elymus Repens Controlmentioning
confidence: 99%
“…However, within the last decade agricultural policies focused increasingly on the integration of CC in arable systems. This has been driven by the 'multifunctional benefits' of CC, including reduction of runoff and soil erosion, increases in soil C sequestration, weed suppression, a reduction in N leaching, and in the case of a legume CC a valuable N source [4,5], and especially Catch crops in the autumn/winter period are mandatory in Denmark, and subsidized in Norway, Sweden, and Finland [6]. Triggered by the 'greening direct payment strategy' in Germany [7], the arable land with CC is also rapidly expanding [8].…”
Section: Introductionmentioning
confidence: 99%
“…Annual dicot weed species were more dominant in NT than in CT in both study years (2016 and 2017). Studies have reported that long‐term NT systems recorded greater total as well as broadleaf weed densities compared to CT (Kadziene et al., 2020; Salonen & Ketoja, 2020). The generally higher densities of winter species compared to summer species in the seedbank can be explained by the absence of weed control measures during the winter fallow season.…”
Section: Resultsmentioning
confidence: 99%